ANALISIS PERAN GURU GEOGRAFI SEBAGAI GURU PENGGERAK DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SMAS PANCA BUDI DAN SMA N 1 NAMORAMBE - Sinurat, Sri Cinta; Lubis, Darwin P (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2025)
This research aims to determine the role of geography teachers as driving teachers in the implementation of the Independent Curriculum at SMAS Panca Budi Medan and SMA N 1 Namorambe. The population in this study were 2 geography subject teachers. Data was collected using interview techniques, documentation and field observation. The data analysis technique is descriptive qualitative. The research results show that: The Merdeka Curriculum emphasizes the concept of independent learning which requires teachers as agents of change to create a supportive learning environment. By referring to the six roles of driving teachers identified by the Ministry of Education and Culture, namely: (a) mobilizing teacher learning communities, (b) developing student-centred learning, (c) building a positive culture in schools, (d) character development, ( e) learning leader in school development, (f) learning and practical community companion.